A low-phase-noise and low-power CMOS colpitts VCO using Gm boosting and capacitance switching techniques - Pakasiri, Chatrpol; You, Jia Hao; Wang, Sen (My University, 2021)
This letter presents a low-power and low-phase-noise 5-GHz VCO fabricated in a standard CMOS 0.18-μm process. The low power dissipation was achieved by using the PMOS cross-coupled pair and Gm-boosting topology, and the low phase noise was obtained by adding two pairs of switched capacitor array. The VCO consumed a dc power of 2.92 mW with the supply voltage of 1 V. The measured phase noises were − 104.6 dBc/Hz and − 117.4 dBc/Hz at 1 MHz offset frequency with switched off and on capacitances, respectively, which demonstrated 12.8-dB improvement.
Keywords: CMOS; Gm-boosting topology; low-phase-noise; low-power; switched capacitor array; voltage-controlled oscillator (VCO)